Adaptation and validation of a Spanish instrument for assessing multicultural competencies and empathy. (July 2021) - Finck, C.; Gómez, Y.; Castro, J.N.; Mogollón, E.Y.; Marcelo, N.; Hinz, A.
Abstract: Purpose of this study was the adaptation and validation of an instrument for the assessment of multicultural outcomes and ethnocultural empathy in Spanish speaking populations. For this purpose, the Everyday Multicultural Competencies Scale / Revised Scale of Ethnocultural Empathy (EMC/RSEE) was chosen. Translation and back translation of the items were conducted resulting in the Spanish version of the scale and were subsequently adapted through cognitive pretesting. For the validation of the scale 485 students responded to an online survey. Results show high reliability and validity for some of the scales, but a general poor fit of the originally proposed six factor solution. An alternative arrangement of 41 items is presented with five factors: Cultural Openness, Conscience of Racism, Empathy, Resentment, and Anxiety. In this arrangement the original factors were maintained, but items relating to empathy, cognition, and emotion, were grouped into a single factor. Possible audiences for the instrument beyond universities are discussed.